1995
DOI: 10.1017/s0033291700033535
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography and single photon emission computed tomography in dementia: a comparative study

Abstract: SYNOPSISA series of elderly patients with dementia of Alzheimer type (AD), multi-infarct dementia (MID) and functional (non-organic) psychiatric illness (major depressive disorder) were selected according to DSM-III-R criteria and received: a battery of cognitive tests, EEG and Single Photon Emission Computed Tomography (SPECT) using 99mTc HMPAO. The EEG and SPECT scans were examined independently of the clinical data. The former were divided into two abnormal categories, those showing AD type change and vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…These findings are considered indirect evidence of the fundamental role of cholinergic system in modulating alpha rhythms, given the well-known selective deficit of acetylcholine occurring from the earliest stages of AD. However, the typical 'slowing' of EEG rhythms seen in AD (Coben et al, 1983(Coben et al, , 1990Sloan et al, 1995) has also been reported in vascular dementia (VaD; Szelies et al, 1992).…”
Section: Introductionmentioning
confidence: 89%
“…These findings are considered indirect evidence of the fundamental role of cholinergic system in modulating alpha rhythms, given the well-known selective deficit of acetylcholine occurring from the earliest stages of AD. However, the typical 'slowing' of EEG rhythms seen in AD (Coben et al, 1983(Coben et al, , 1990Sloan et al, 1995) has also been reported in vascular dementia (VaD; Szelies et al, 1992).…”
Section: Introductionmentioning
confidence: 89%
“…By discriminant analysis on qEEG and rCBF performed on the same sample of patients but considered in a separate analysis, sensitivity was shown to reach 77% for qEEG and 63% for perfusional SPECT, while specificity scored 93% for qEEG and 88% for SPECT [30]. In a qEEG/PET study on AD patients and normal controls, accuracy values of 86% for temporoparietal relative theta power and of 87% for rCMRGlu were reported, whereas in the mild AD subgroup the corresponding figures were 66.7 and 75% [12].…”
Section: Discriminant Analysismentioning
confidence: 98%
“…Moreover, even in the field of AD, some attempts have recently been made in order to assess the relationships between EEG and metabolism, and to evaluate whether these parameters may increase the ability to detect pathological changes even in most subtle cases [12,30].…”
Section: Introductionmentioning
confidence: 99%
“…AD patients were characterized by higher delta (0 -3 Hz), higher theta (4 -7 Hz), lower posterior alpha (8 -12 Hz), slowing in alpha peak frequency, and lower beta (14 -30 Hz) and gamma (around 40 Hz) (Dierks et al, 1993Huang et al, 2000;Wolf et al, 2003;Babiloni et al, 2004;Moretti et al, 2004;Adeli and GhoshDastidar, 2005). The abnormality of EEG rhythms in dementia has been associated with altered rCBF/metabolism and cognitive function (Szelies et al, 1992;Julin et al, 1995;Passero et al, 1995;Sloan et al, 1995;Rodriguez et al, 1999aRodriguez et al, , 1999b. Furthermore, parieto-temporal EEG rhythms and rCBF have been correlated with severity of AD as measured by Mini Mental State Evaluation scores (MMSE).…”
Section: Introductionmentioning
confidence: 99%